Newer condylar trapezoidal plate in treatment of mandibular condyle fractures : short clinical study - Passi, Deepak; Gupta, Ritu; Chandra, Lokesh; Singh, Abhishek; sharma, Prarthana; Yadav, Garima (International Journal of Dental Research, 2017)
Mandibular condyle fracture is one of the most frequent injuries of the facial skeleton. The treatment ofmandibular condyle is either closed reduction or open reduction with internal fixation. The open reduction of mandibular condyle fractures has become more favorable and gaining popularity since various osteosynthesis materials and techniques were developed in the past few decades. These include fixation with Kirschner wires, intraosseous wiring, miniplates, and lag screw fixation. In response to a increased number of needs for improved treatment in this region, a variable morphological plates have been developed with specific designs to treat such fractures. We present a case series of use of new condylar trapezoidal plate (condylar fragment plate) in the treatment of mandibular condyle fractures.